Answer:
Step-by-step explanation:
75
Answer:
The factorized form of the given expression is
Step-by-step explanation:
Given;
4a² + b² - 4ab - 8a + 4b + 4
This expression is factorized as follows;
(4a² - 8a + 4) + (b² - 4ab + 4b)
(4a² - 4a - 4a + 4) + b² - 4b(a - 1)
(4a - 4)(a - 1) + b² - 4b(a - 1)
(4a - 4)(a - 1) - 4b(a - 1) + b²
4(a - 1)(a - 1) - 4b(a - 1) + b²
4(a - 1)² - 4b(a - 1 + b/4)
Answer:
x must equal 5 and y must equal 2
therefore,
5a + 2b = 23 and
5a - 2b = 7.
I'm gonna take 5a + 2b = 23 and add 7 to each side:
5a + 2b + 7 = 30
and substitute 5a -2b in for 7 on the left side:
5a + 2b + (5a-2b) = 30
10a = 30
a = 3
Now we know a. Now take
5a -2b = 7
and substitute in 3 for a
5*(3) - 2b = 7
15 -2b = 7
8 = 2b
b = 4
a = 3 and b = 4
Step-by-step explanation:
7sqrt = 49 since the base is a square.
49 x 2 = 98 - since there's 2 of those identical squares.
7 x 5 = 35 - area of the rectangular face.
35 x 4 = 140 - since there's 4 of those faces.
140 added by 98 is 238.
So answer is B.
Answer:
6 6/7 km/h
Step-by-step explanation:
The relations between speed, time, and distance are ...
time = distance/speed
speed = distance/time
__
So, to find the average speed, we need to know the total distance and the total time. The distances are given, but we need to compute the times.
time jogging = (2 km)/(8 km/h) = 1/4 h
time walking = (2 km)/(6 km/h) = 1/3 h
Then the woman's average speed is ...
average speed = (total distance)/(total time) = (2 km + 2 km)/(1/4 h + 1/3 h)
= (4 km)/(7/12 h) = 48/7 km/h
= 6 6/7 km/h